Committed Tuppence-worth: When Celebrities Dabble in Scottish Politics - Wirth, Robert (L'engagement en Ecosse autour de l'enjeu de l'indépendance)

Present and Absent Nostalgia in the 2014 Referendum (Journal of Scottish Thought: If Scotland ...Conjecturing 2014)

Jürs-Munby, K. / Carroll, J. / Giles, S. (Hg.): Postdramatic Theatre and the Political - Tönnies, Merle (Journal of Contemporary Drama in English)

Between Authenticity and Objectification: Narrating the Self in Contemporary British Drama - Tönnies, Merle (Dramatic Minds. Performance, Cognition, and the Representation of Interiority)

Committed Tuppence-worth: When Celebrities Dabble in Scottish Politics - Wirth, Robert (Le 55e congrès de la Société des Anglicistes de l’Enseignement Supérieur)

Racing in the City: Spatial Relationships in Alan Bissett’s Boyracers - Wirth, Robert (Place and Space in Scottish Literature and Culture)

Kamm, J. / Lenz, B. (Hg.): Representing Terrorism and Deconstructing Terrorism - Tönnies, Merle (Arbeiten aus Anglistik und Amerikanistik)

Wiki-Wonderland? – Eine Qualitative Analyse zu Vor- und Nachteilen von Wikis für Lehrende und Studierende - Flotmann, Christina (Lehr- und Lernpraxis im Fokus – Forschungs- und Reflexionsbeiträge aus der Universität Paderborn)

Political Rhetoric as a Structural and Ideological Instrument in Star Wars and Harry Potter - Flotmann, Christina (Politics in Fantasy Media: Essays on Ideology and Gender in Fiction, Film, Television and Games)

(En-)Gendering a Popular Theatrical Genre. The Roles of Women in Nineteenth-Century British Melodrama - Tönnies, Merle

Anti-hegemoniale Strategien des Kleinen. Britische dokumentarische Farbfotografie als Kritik des Thatcherismus - Tönnies, Merle (Kulturen des Kleinen. Mikroformate in Literatur, Kunst und Medien)

Nostalgia: The Elephant in the Room of the Scottish Independence Debate - Wirth, Robert (Transcending Oppositions in Scottish Culture: A Symposium)

Heading towards an Unpredictable Past: Nostalgia in the Scottish Independence Debate - Wirth, Robert (IF SCOTLAND)

Middeke,M. / Schnierer, P.P. / Sierz, A. (Hg.): The Methuen Guide to Contemporary British Playwrights - Tönnies, Merle (Anglia)

Rossow, H. Globalismus und Lew Labour - Tönnies, Merle (Anglistik. International Journal of English Studies)

Baumbach, S. / Neumann, B. / Nünning, A.: A History of British Drama - Tönnies, Merle (Anglistik. International Journal of English Studies)

"This Bright Inward Cinema of Thought" – Stream of Consciousness in Contemporary English Fiction - Strauß, Sara

‘Monstrous’ Homes: How Private Spaces Shape Characters’ Identities in 19th-century Sensation Fiction - Flotmann, Christina (Monstrous Geographies: Places and Spaces of the Monstrous)

Ambiguity in ‘Star Wars’ and ‘Harry Potter’: A (Post-)Structuralist Reading of Two Popular Myths - Flotmann, Christina

Populäre Mythen bei Star Wars und Harry Potter - Flotmann, Christina
Interview 2 Feb. 2013